Agents of God: boundaries and authority in Muslim and Christian schools - Guhin, Jeffrey Joseph (Oxford University Press, 2021)
1. Authority and Essence -- 2. Politics and Public Schools -- 3. Differently Differentiating Gender -- 4. Sex and the Internet -- 5. Scripture as External Authority -- 6. Prayer as External Authority -- 7. Science as External Authority -- 8. It's Dangerous Out There -- Methodological Appendix -- Endnotes -- Bibliography .